2009
DOI: 10.1089/jop.2009.0026
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Surface Distribution and Pharmacokinetics of a Novel Ophthalmic 1% Azithromycin Formulation

Abstract: Sustained and high concentrations were encountered with 7-day approved administration of 1% azithromycin formulation (AzaSite, Inspire Pharmaceuticals, Inc., Durham, NC) within all ocular surface tissues, particularly the lids. Many ocular surface disorders involving the tear film, eyelids, and adnexal structures are associated with chronic, low-grade bacterial infection and may potentially lead to decreased vision secondary to corneal scarring. Various topical antibiotic and steroid combinations with or witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 17 publications
5
51
0
Order By: Relevance
“…To the best of our knowledge, there is no published study assessing the efficacy of Azyter ® in blepharitis. Although most of the studies that evaluate azithromycin in blepharitis used AzaSite ® (Inspire Pharmaceuticals, Inc, Durham, NC, USA), our results are comparable (8,1921) . AzaSite ® is …”
supporting
confidence: 51%
“…To the best of our knowledge, there is no published study assessing the efficacy of Azyter ® in blepharitis. Although most of the studies that evaluate azithromycin in blepharitis used AzaSite ® (Inspire Pharmaceuticals, Inc, Durham, NC, USA), our results are comparable (8,1921) . AzaSite ® is …”
supporting
confidence: 51%
“…14) Following the U.S. Food and Drug Administration (FDA)-approved regimen of 1 drop twice daily for 2 d followed by 1 drop daily for 5 d, topical azithromycin reached a maximum concentration of 180 µg/g of tissue in the rabbit eyelid. 15) However, our LC-MS-based bioanalysis revealed that azithromycin concentration in the meibomian glands was sub-inhibitory at 0.8 µg/g tissue after a single instillation. This is probably because our protocol enabled precise meibomian gland collection without surface contamination, resulting in much lower concentrations.…”
Section: Discussionmentioning
confidence: 79%
“…Various treatment options for MGD including the LipiFlow instrument, intense pulsed light, eyelid-warming devices, intraductal probing, as well as topical or oral application of drugs have been developed [11][12][13][14][15][16][17][18][19]. Our present results regarding additional instruction by nurses for improving the outcome of treatment with the Azuki-no-chikara eyelid-warming device may also be applicable to other treatment approaches.…”
Section: Resultsmentioning
confidence: 97%